Coronary artery disease and revascularization associated with immune checkpoint blocker myocarditis: Report from an international registry. (December 2022) - Nowatzke, Joseph; Guedeney, Paul; Palaskas, Nicholas; Lehmann, Lorenz; Ederhy, Stephane; Zhu, Han; Cautela, Jennifer; Francis, Sanjeev; Courand, Pierre-Yves; Deswal, Anita; Ewer, Steven M.; Aras, Mandar; et al.
Abstract: Purpose: Immune checkpoint blocker (ICB) associated myocarditis (ICB-myocarditis) may present similarly and/or overlap with other cardiac pathology including acute coronary syndrome presenting a challenge for prompt clinical diagnosis. Methods: An international registry was used to retrospectively identify cases of ICB-myocarditis. Presence of coronary artery disease (CAD) was defined as coronary artery stenosis >70% in patients undergoing coronary angiogram. Results: Among 261 patients with clinically suspected ICB-myocarditis who underwent a coronary angiography, CAD was present in 59/261 patients (22.6%). Coronary revascularization was performed during the index hospitalisation in 19/59 (32.2%) patients. Patients undergoing coronary revascularization less frequently received steroids administration within 24 h of admission compared to the other groups (p = 0.029). Myocarditis-related 90-day mortality was 9/17 (52.7%) in the revascularised cohort, compared to 5/31 (16.1%) in those not revascularized and 25/156 (16.0%) in those without CAD (p = 0.001). Immune-related adverse event-related 90-day mortality was 9/17 (52.7%) in the revascularized cohort, compared to 6/31 (19.4%) in those not revascularized and 31/156 (19.9%) in no CAD groups (p = 0.007). All-cause 90-day mortality was 11/17 (64.7%) in the revascularized cohort, compared to 13/31 (41.9%) in no revascularization and 60/158 (38.0%) in no CAD groups (p = 0.10). After adjustment of age and sex, coronary revascularization remained associated with ICB-myocarditis-related death at 90 days (hazard ratio [HR] = 4.03, 95% confidence interval [CI] 1.84–8.84, p < 0.001) and was marginally associated with all-cause death (HR = 1.88, 95% CI, 0.98–3.61, p = 0.057). Conclusion: CAD may exist concomitantly with ICB-myocarditis and may portend a poorer outcome when revascularization is performed. This is potentially mediated through delayed diagnosis and treatment or more severe presentation of ICB-myocarditis. Highlights: ICB-myocarditis can clinically present similarly to acute coronary syndrome. Diagnostic steps are similar; treatment of both entities is substantially different. Delay in appropriate treatments of severe ICB-myocarditis should be avoided.